The tectonic evolution of the Irtysh tectonic belt: New zircon U–Pb ages of arc-related and collisional granitoids in the Kalaxiangar tectonic belt, NW China - Hong, Tao; Klemd, Reiner; Gao, Jun; Xiang, Peng; Xu, Xing-Wang; You, Jun; Wang, Xin-Shui; Wu, Chu; Li, Hao; Ke, Qiang (Lithos, 2017)
Precise geochronological constraints of the Irtysh tectonic belt situated between the Saur Island Arc and the Altay Terrane are crucial to a better understanding of the tectonic evolution of the Central Asian Orogenic Belt (CAOB). Recently, we discovered repeatedly deformed arc-related and collisional granitoids in the Kalaxiangar tectonic belt (KTB), which is located in the eastern part of the Irtysh tectonic belt. In this study, we report new whole-rock geochemical, zircon U–Pb and Hf isotopic data of the arc-related and collisional granitoids. Our data reveal that 1) arc-related granodioritic porphyries formed at ca. 382–374 Ma. Recrystallized zircon grains from a (ultra-)mylonitic granodiorite of the Laoshankou zone in the southern KTB display a U–Pb age of ca. 360 Ma; 2) syn-collisional granodioritic porphyries, which distribute along faults and parallel to the cleavage, were emplaced at ca. 367–356 Ma, with εHf(t) values varying from + 7.8 to + 14.2 and Hf model ages from 873 to 459 Ma; 3) a post-collisional A-type granodioritic porphyry, which crosscuts the NW-NNW trending schistosity of the metasedimentary country rocks at a low angle, has an age of ca. 324–320 Ma, while the εHf(t)values range from + 7.6 to + 14.4 with Hf model ages from 850 to 416 Ma; 4) post-collisional strike-slip A-type granite dykes, exposed along strike-slip faults, gave ages between 287 and 279 Ma, whereas the εHf(t) values range from + 4.9 to + 12.7 and the Hf model ages from 995 to 500 Ma; and 5) A-type biotite granite dykes, which intruded along conjugate tension joints, have ages of 274–271 Ma, and εHf(t) values from + 1.5 to + 13.2 with Hf model ages from 1196 to 454 Ma. Consequently, we propose that the collision between the Saur Island Arc and the Altay Terrane occurred in the Early Carboniferous (ca. 367–356 Ma) and the subsequent post-collisional tectonic process continued to the Late Carboniferous (ca. 324–320 Ma). It is further suggested that the Irtysh tectonic belt underwent large-scale strike-slip deformation during the mid-Permian between 287 and 279 Ma. The termination of the Irtysh tectonic belt orogeny is thought to have also occurred during the mid-Permian between 274 and 271 Ma.
Keywords: Zircon U–Pb age; Arc-related and collisional granitoids; Tectonic evolution; Irtysh tectonic belt